PENGARUH KUALITAS PRODUK, HARGA, DAN CITRA MEREK TERHADAP MINAT BELI SMARTPHONE APPLE: Studi Kasus Pada Kelurahan Limo Depok - Ramadini Triastari, - (2019)
This research is a quantitative that aims to determine the effect of quality product, price and brand image to interest buying. Population in this research is society of Kelurahan Limo Depok. The variables used in this research are quality product, price and brand image to interest buying independent variable, then interest buying as dependent variable. The sample size was taken 75 respondents, with nonprobability sampling method, especially purposive sampling. Data collection was done through questionnaires. In this research, three hypotheses will be tested using PLS (Partial Least Square) analysis tool. Based on the results of data processing with PLS (Partial Least Square) has the result that (1) quality product an effect on interest buying with t-statistics of 0.000. (2) price has no effect on interest buying with a t-statistic value of 0.950. (3) brand image an effect on interest buying with t-statistic value of 0,000.